PELATIHAN PEMANFAATAN TEKNOLOGI RAMAH LINGKUNGAN DALAM PEMBUATAN BIBIT PISANG SEHAT DI DESA KUKUH TABANAN - SUNITI, N. W. (Buletin Udayana Mengabdi; Vol 7 No 2 (2008): Volume 7 No.2 – September 2008, 2012)
ABSTRACT Training to made the healthy banana seed and control of banana wild disease with Persada biopesticide and Biota-L botanical pesticide was held at Kukuh village District of Kerambitan, Tabanan regency on 20 Juli 2008. Their activities were aimed to improve the farmer knoledge of banana wild disease and made the banana healthy seed and control the banana wild disease. The topics covered were symptom, bioecology, fungal distribution, control of banana wild disease and made the banana healthy seed with Persada biopesticide and Biota-L botanical pesticide. The training was attended by 20 participants from lokal farmer of Kukuh village. The method use in activities were lecture, trainning to made banana healthy seed. All farmer were intrrested in this program and hope be continued for the future,